1996
DOI: 10.1074/jbc.271.46.28818
|View full text |Cite
|
Sign up to set email alerts
|

The α3β3γ Subcomplex of the F1-ATPase from the Thermophilic Bacillus PS3 with the βT165S Substitution Does Not Entrap Inhibitory MgADP in a Catalytic Site during Turnover

Abstract: The hydrolytic properties of the mutant ␣ 3 (␤T165S) 3 ␥ and wild-type ␣ 3 ␤ 3 ␥ subcomplexes of TF 1 have been compared. Whereas the wild-type complex hydrolyzes 50 M ATP in three kinetic phases, the mutant complex hydrolyzes 50 M ATP with a linear rate. After incubation with a slight excess of ADP in the presence of Mg 2؉ , the wild-type complex hydrolyzes 2 mM ATP with a long lag. In contrast, prior incubation of the mutant complex under these conditions does not affect the kinetics of ATP hydrolysis. The A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 57 publications
4
86
0
Order By: Relevance
“…The observation that carboxymethylation of ␣ 3 (␤E201C) 3 ␥ increases k cat and K m3 provides additional support for this hypothesis. Also consistent with this hypothesis are earlier reports demonstrating that the ␤T165S substitution in TF 1 increases K m3 and k cat (23,24). Replacement of threonine by serine in this position might decrease the affinity of MgATP bound to closed catalytic sites by interacting less strongly with Mg …”
Section: Discussionsupporting
confidence: 78%
“…The observation that carboxymethylation of ␣ 3 (␤E201C) 3 ␥ increases k cat and K m3 provides additional support for this hypothesis. Also consistent with this hypothesis are earlier reports demonstrating that the ␤T165S substitution in TF 1 increases K m3 and k cat (23,24). Replacement of threonine by serine in this position might decrease the affinity of MgATP bound to closed catalytic sites by interacting less strongly with Mg …”
Section: Discussionsupporting
confidence: 78%
“…PS3 also entraps an inhibitory Mg-ADP in a catalytic site, resulting in enzyme inhibited for ATP hydrolysis (31). However, this entrapped Mg-ADP in the F 0 F 1 is capable of being released from the catalytic site (32,33). Thus, the F 0 F 1 from PS3 can catalyze both the ATP synthesis/hydrolysis directions.…”
Section: Discussionmentioning
confidence: 99%
“…Many years ago we have reported that ADP(Mg2+)-deactivated F~-Fo ATPase is capable of ATP synthesis [20] and concluded that the inhibitory ADP binds to a site which is not the same as that where ADP leaves F~ during the steady-state ATP hydrolysis [12,20]. Much effort have been put forward over past 15 years to attribute ADP-specific inhibition to catalytic or non-catalytic ATPase sites but clear-cut consensus does not appear to be reached ( [33][34][35][36] and references cited therein). The results presented in this report strongly support and reinforce our original observation on the catalytic competence of ADP(Mg 2+) inhibited F~-F 0 ATPase in ATP synthesis.…”
Section: Discussionmentioning
confidence: 99%